Reinterpretasi Ayat-Ayat tentang Relasi Gender dalam Keluarga - Matswah, Akrimi (Lajnah Pentashihan Mushaf Al-Qur'an, 2014)
The Issue of gender in family basically has become an interesting issue to study. It is because, in fact, the problem related to gender relations in family is often studied only from the theoretical aspect and is not fully implemented in practical life. Therefore, the role of the family law which is got from the understanding on the religious text as the guidance for the humankind becomes absolutely important to be studied and implemented continuously. In relation to this, it is necessary to study the thought Edip Yuksel, et all, the Muslim contemporary thinkers who translated and interpreted the Qur'an as they are reflected in their work: Qur'an: A Reformist Translation. A Renewal in the field of Qur'an interpretation and translation based on the principle of Gender equality (al-musÃ„ÂwÃ„Âh al-jinsiyyah). Thus, the explanation about their interpretations concerning gender relation in the family as the issue studied in this writing is hoped to be able to give contribution in the study of family law in Indonesia.